Her-2 Expression Status in Different Histopathological Grades of Urothelial Carcinoma - Ayesha Imtiaz Malik, Rukhsana Jabeen, Attya Zaheer, Nazma Kiran, Nazia Siddique (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Urothelial carcinoma is the predominant histological sub-type and accounts for 90% of human urinary bladder cancers. It is among the ten common malignancies of adults in Pakistan. Her-2 receptor modifications including mutations have been previously evaluated as one of the major players in carcinogenesis of urinary bladder’s carcinoma arising from urothelium. The increase in expression of Her-2 receptor is seen in higher grade carcinomas along with muscle infiltration in comparison to tumors of lesser grade and not invading muscle layer. Aims and Objectives: To compare epidermal growth factor (Her-2) receptor expression status between high and low grade, infiltrative and non-infiltrating carcinoma of urinary bladder’s urothelium. Materials and Methods: 50 cases with diagnosis of primary papillary urothelial carcinoma with variable stages and grades, from both genders and different ages, were selected using convenience sampling for current cross sectional study. Routined protocols opted for immunohistochemical staining to observe Her-2 expression in urothelial cancer trans-urethral resection specimen. If more than 10 percent of cells with positive circumferential complete, and intense membrane staining for Her-2 were taken as positive as assessed semi-quantitatively by using immuno-reactive scoring system designated by ASCO/CAP guidelines. Results: Patients having ages ranging from 42 to 95 years including 37 males and 13 females were selected for current study. Her-2 immunostaining revealed, positivity in 27 (54%) patients. Results interpreted showed more number of cases having higher grade (p= 0.0006) and infiltration (p = 0.0001) with Her-2 positivity. Conclusions: The current study showed significant amount of Her-2 positivity in greater grade and carcinomas possessing muscle invasion as compared to tumors of lower grade and those not invading muscle wall.